Enriching oil palm industry through American oil palm - Murugesan, P; Sunilkumar, K (Indian Horticulture, 2015)
The Elaeis oleifera species is extensively used in advanced crop improvement programmes as they have desirable traits, viz. slow vertical growth, superior oil quality and disease tolerance. To introgress oil quality, low height increment traits, of Elaeis oleifera into Elaeis guineensis, two species were hybridised to produce OÃ—G hybrids. Interspecific hybridization programme has been initiated at Directorate of Oil Palm Research with the objectives of high fruit and oil production per unit of area, low height increment and oil with higher content of unsaturated fatty acids and carotenes. Indigenously developed Elaeis oleifera crosses showed precocity for bunch production and recorded very low annual height increment with normal fruit set and high sex ratio. There is an urgent need to collect new materials from centres of origin by exploration and exchange through unilateral and multilateral collaborative programmes for broadening genetic base for development of new varieties in oil palm.